Simulating clamp placement across the trans-syndesmotic angle of the ankle to minimize malreduction: A radiological study. Issue 3 (March 2017) - Putnam, Sara M.; Linn, Michael S.; Spraggs-Hughes, Amanda; McAndrew, Christopher M.; Ricci, William M.; Gardner, Michael J.
Abstract: Background: Ankle fractures associated with syndesmotic injury have a poorer prognosis than those without such an injury. Anatomic reduction of the distal tibiofibular joint restores joint congruency and minimizes contact pressures, yet operative fixation of syndesmotic ankle injuries is frequently complicated by malreduction of the syndesmosis. Current methods of assessing reduction have been shown to be inadequate. As such, additional methods to judge the accuracy of syndesmotic reduction are required. Questions/Purposes: The purposes of our study were (1) to determine the anatomic axis of the syndesmosis, or the trans-syndesmotic angle (TSA), and (2) to describe the intraoperative fluoroscopic appearance of syndesmotic clamp reduction oriented along the anatomic syndesmotic angle. Methods: Computed tomography (CT) scans of 45 uninjured adult ankles were analyzed to measure the TSA, defined as the angle between the plane of a lateral ankle radiograph and a line drawn perpendicular to the fibular incisura. Three-dimensional reconstructions of CT scans were then used to demonstrate clamp placement collinear with the TSA as would be seen on an intraoperative lateral ankle radiograph. Results: The average TSA measured 21 ± 5° anterior to the plane of a lateral radiograph. When a simulated reduction clamp tine was placed on the fibular ridge and the clamp oriented along the TSA, the medial tine, as seen on a lateral radiograph, was within the anterior one-third of the tibia 93% of the time. It was, on average, 23 ± 7% of the distance from the anterior to the posterior tibial cortex, with tine placement occurring in this range in 73% of ankles. The medial tine rested 53 ± 17% of the distance between the anterior cortices of the tibia and fibula, with 71% of tines placed in this range. Conclusions: Reduction clamp placement oriented along the TSA has a predictable appearance on lateral ankle imaging and can guide clamp positioning during syndesmotic reduction. With one tine placed on the fibular ridge, placing the medial clamp tine in the anterior third of the tibia, or halfway between the anterior cortices of the tibia and fibula is the most accurate position for reduction in line with the TSA. Level of evidence: 2 (Retrospective diagnostic).